Detecting the cosmological neutrino background in the CMB - Sellentin, Elena; Durrer, Ruth (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
Three relativistic particles in addition to the photon are detected in the cosmic microwave background (CMB). In the standard model of cosmology, these are interpreted as the three neutrino species. However, at the time of CMB decoupling, neutrinos are not only relativistic but they are also free-streaming. Here we investigate whether the CMB is sensitive to this defining feature of neutrinos, or whether the CMB data allow us to replace neutrinos with a relativistic fluid. We show that free-streaming particles are preferred over a relativistic perfect fluid with Δχ2≃21. We then study the possibility to replace the neutrinos by a viscous fluid and find that also a relativistic viscous fluid with either the standard values c2eff=c2vis=1/3 or best-fit values for c2eff and c2vis has Δχ2≃20 and thus cannot provide a good fit to present CMB data either.
Gesehen am 16.06.2020